Climate Stress, Inflation, and Foreign Investment: Do Growth and Corruption Control Shape Inequality? - Zahara, Riska; Majid, M Shabri Abd; Abrar, Muhammad (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study provides a new contribution by examining climate stress, inflation, and foreign investment within a single integrated framework. By uniting environmental, macroeconomic, and governance factors, it offers a clearer understanding of the structural drivers of inequality in ASEAN-4. Research Objectives: The study examines the impacts of climate change, inflation, and foreign investment on inequality and evaluates how economic growth and corruption control moderate these effects. Research Methods: The study uses annual panel data for Indonesia, Malaysia, Thailand, and the Philippines from 2002 to 2023 and applies moderated panel regression analysis to estimate both direct and interaction effects. Empirical Results: Climate pressures and foreign investment increase inequality, while inflation slightly reduces it. The analysis also shows that economic growth lessens the inequality effect of foreign investment, whereas stronger corruption control unexpectedly amplifies it, suggesting that better governance does not automatically ensure fairer investment outcomes. Implications: These findings suggest that ASEAN-4 policymakers must align inclusive growth, inflation stability, environmental action, and improved governance to effectively reduce inequality and support sustainable development. JEL Classification: D63, E31, F21, O44, O43